Understanding strabismus - Irfan, Sameera; Akram, Amjad (New Delhi India : Jaypee Brothers Medical Publishers, 2014)
The subject of strabismus is like a vast ocean; standing by its shores, one cannot assess its full expanse but only by taking a deep plunge into it does one realize its true depth an dimension.
Contents Chapter 1: Assessment of Strabismus Chapter 2: Refractive Errors Chapter 3: Amblyopia Chapter 4: Essential infantile Esotropia Chapter 5: Esotropia y other more...
Incluye dos ejemplares
Incluye índice
Incluye ilustraciones a colores
Keywords: OFTALMOLOGÍA; OPHTHALMOLOGY; ESTRABISMO; OJOS -- TRASTORNOS DEL MOVIMIENTO